Molecular and Clinical Characterization of LAG3 in Breast Cancer Through 2994 Samples - Liu, Qiang; Qi, Yihang; Zhai, Jie; Kong, Xiangyi; Wang, Xiangyu; Wang, Zhongzhao; Fang, Yi; Wang, Jing (Frontiers in Immunology, 2021)
Despite the promising impact of cancer immunotherapy targeting CTLA4 and PD1/PDL1, a large number of cancer patients fail to respond. LAG3 (Lymphocyte Activating 3), also named CD233, is a protein Coding gene served as alternative inhibitory receptors to be targeted in the clinic. The impact of LAG3 on immune cell populations and co-regulation of immune response in breast cancer remained largely unknown. To characterize the role of LAG3 in breast cancer, we investigated transcriptome data and associated clinical information derived from a total of 2994 breast cancer patients. We estimated the landscape of relationship between LAG3 and ten types of cell populations in breast cancer. We investigated the correlation pattern between LAG3 and immune modulators in pan-cancer, especially the synergistic role of LAG3 with other immune checkpoints members in breast cancer. LAG3 expression was closely related to malignancy of breast cancer and might serve as a potential biomarker; LAG3 might plays an important role in regulating tumor immune microenvironment, not only T cells, but also other immune cells. More importantly, LAG3 might synergize with CTLA4, PD1/ PDL1 and other immune checkpoints, thereby lending more evidences to combination cancer immunotherapy by targeting LAG3, PD1/PDL1, and CTLA4 together.